Understanding Consumer Intention to Purchase Biodegradable Plastic Bags: The Roles of Green Awareness, Subjective Norms, and Green Trust - Budiarta, I Nengah Gina; Usadi, Made Pradnyan Permana; Tresnasari, Ni Kadek Asti; Laksmiani, Ni Luh Komang Putri (Philippine Social Science Journal, 2025)
To address the persistent issue of household plastic waste in Denpasar City, Bali, this study examines the influence of green awareness and subjective norms on the intention to adopt biodegradable plastic bags, mediated by green trust. Employing a quantitative design with 100 respondents and Structural Equation Modeling, the analysis reveals that both awareness and social norms significantly enhance green trust, which in turn drives purchase intention. The findings identify green trust as a crucial psychological bridge connecting environmental concern to sustainable behavior. Practically, these results suggest that local stakeholders can accelerate the shift toward sustainable packaging by fostering public awareness and supportive social norms. Future research should investigate behavioral barriers, such as cost and habit, and employ qualitative or comparative approaches to deepen understanding.